What lessons can we learn? Clinical and epidemiological retrospective analysis of 267 patients with urticaria in a Brazilian tertiary center - Roberta Fachini Jardim Criado; Paulo Ricardo Criado; Nathalia Baldavira; Debora Cardial; Ana Maria Gimenez-Arnau; Carlos D'Apparecida Machado Filho (Sociedade Brasileira de Dermatologia, 2021)
Abstract Background: There are few epidemiological studies of urticaria, published in the indexed literature (PubMed/Medline). Objective: The study aimed to evaluate the epidemiological and clinical data among patients with urticaria/angioedema attending a reference clinic in Brazil. Methods: Two hundred sixty-seven patients were evaluated retrospectively considering demographic data, time course of the disease, triggering symptoms, the presence of angioedema, complementary laboratory tests including total blood count, reactive-C protein, erythrocyte sedimentation rate, IgE serum levels, and other, as necessary. Results: The most commonly diagnosed type of urticaria was chronic spontaneous urticaria (56.93%). Angioedema was associated with chronic urticaria in 108 patients (40.08%). Study limitations: Unicentered and retrospective. Conclusion: Some relevant findings in this study are the observation of a female prevalence of cases (4-females: 1-man), a result more elevated than demonstrated in previous studies in Europe and Asia, the median age was 43-years old and the delay of time between the diagnosis of urticaria and the admission for treatment in a specialized center was approximately 2-years. Other multicenter studies can better establish these differences in Brazilian patients.